Menggugat Menggugat Keadilan Poligami Dalam Hukum Perkawinan Di Indonesia Perspektif Gender - Mas adah Mas adah (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2026)
Polygamy is in the spotlight of the law and Indonesian society as a legal state has regulated polygamy as a legal marriage and has a legal umbrella, namely the Marriage Law. The polygamy procedure in the Marriage Law has imposed requirements for husbands who want to commit polygamy with the conditions: husbands must have permission from their wives, officials (for civil servants) and the court as the final stage to obtain a polygamy permit. However, the court will not grant permission for polygamy unless the husband can fulfill the alternative requirements: the wife cannot perform her duties as a wife, the wife has an incurable disease and the wife cannot give birth. It appears that the wife is the object of polygamy and there is an inconsistency where the principle of marriage is monogamous but still provides a loophole for polygamy. This research aims to criticize the Marriage Law in Indonesia which regulates polygamy from a gender perspective. The method used by the author in writing is descriptive normative legal research method, the result of this research analysis is that the Marriage Law in Indonesia in regulating polygamy looks unjust or impartial to women and views women as sub ordinate.